White perovskite based lighting devices. Issue 59 (28th June 2018) - Bidikoudi, M.; Fresta, E.; Costa, R. D.
Abstract : Hybrid organic–inorganic and all-inorganic metal halide perovskites have been one of the most intensively studied materials during the last few years. Abstract : Hybrid organic–inorganic and all-inorganic metal halide perovskites have been one of the most intensively studied materials during the last few years. In particular, research focusing on understanding how to tune the photoluminescence features and to apply perovskites to optoelectronic applications has led to a myriad of new materials featuring high photoluminescence quantum yields covering the whole visible range, as well as devices with remarkable performances. Having already established their successful incorporation in highly efficient solar cells, the next step is to tackle the challenges in solid-state lighting (SSL) devices. Here, the most prominent is the preparation of white-emitting devices. Herein, we have provided a comprehensive view of the route towards perovskite white lighting devices, including thin film light-emitting diodes (PeLEDs) and hybrid LEDs (HLEDs), using perovskite based color down-converting coatings. While synthesis and photoluminescence features are briefly discussed, we focus on highlighting the major achievements and limitations in white devices. Overall, we expect that this review will provide the reader a general overview of the current state of perovskite white SSL, paving the way towards new breakthroughs in the near future.